200 Learning from the lived experience of COVID-19: parental healthcare seeking behaviour for children with asthma. (17th August 2022) - Rogers, Amy
Abstract : CDDFT Aims: Explore the meaning of the COVID-19 pandemic for parents of children with asthma in relation to healthcare seeking for their child. Methods: Interpretive phenomenological analysis (IPA) – allows researcher to focus on personal meaning in a particular context (healthcare seeking), for people (parents of children with asthma), who share a particular experience (COVID-19 pandemic). IPA ensures congruence between researcher paradigm, philosophical stance, personal stance, positionality statement, phenomenon to be studied, data collection method, and analysis. Eligibility criteria: Parents of a child (2-16 years) with a diagnosis of asthma. Parents of a child with a diagnosis of asthma without other respiratory conditions Parents of a child with asthma not associated with prematurity (gestation >37/40) or chronic lung disease. Parents of a child with asthma and any of the following co-morbidities: eczema, hay-fever or food allergies (atopy) Parents who are able to read and speak English Data collection and analysis: Unstructured interviews lasting 30-60mins, recorded using Zoom. Transcripts transcribed verbatim and uploaded to Nvivo – data coded using descriptive, linguistic and conceptual comments. Codes mapped in to groups according to inter-relatedness, an iterative and interpretive process using deconstruction, reconstruction and re-organisation of text to identify themes Results: Themes identified 1. Protecting the child: mothers' perception of threat from COVID-19, and what this meant they needed to do, to protect their child. 2. Balancing needs and conflicts of interest: the difficulty mothers' face in trying to balance the physical, mental, and emotional health needs of the child with the need to socialise, go to school, and learn; and for mothers that needed to go to work, the conflict of interest this created 3. Accessing healthcare: the positive influence of knowledge and experience on the speed of accessing healthcare, the barrier of timing in relation to availability of service, and the effort required to access services 4. Being heard, understood and responded to: mothers' perception of not being heard, understood or responded to whilst seeking healthcare for their child and the psychological consequences that result 5. Changing perception of risk over time: the changing perception of risk to the child's health during the pandemic, as related to perception of reality. Conclusion: During a pandemic, information conveyed to parents needs to be updated in line with emerging evidence. Parents may be operating on high alert - it is not sufficient to issue the message that the NHS is still available. The importance of face-to-face consultations for worried and stressed parents should not be under-estimated and where this is not possible, video consultations should supersede other forms of communication so that information is not lost in translation and parents feel heard and understood. Wider society should implement good hand hygiene, social distancing and face masks when they have a viral infection, to protect those around them. Healthcare professionals need to recognise the daily burden of asthma for mothers, who are always on the look-out for symptoms, and the fear that an acute exacerbation can induce. Management should include emotional support as well as medical, to ensure parents feel in control and able to manage.